THE VISION ABOUT INTERNATIONAL SECURITY AT THE BEGGINING OF THE XXI CENTURY - Flavius-Cristian, Marcau; Andreea, Ciorei Mihaela (European Scientific Journal, ESJ, 2013)
In the interaction of people, politics appears each time when there is a dispute over the expected results of two or more actors inter- addicted -they or their agents- by different angle their interests, goals and values. But there are no differences or conflicts, then there is no policy, as long as people preferences and the affirmations of the will to meet them in conflict, there doesn’t exist politics. Security is a special policy form - a species of the genus more general of policy, all aspects of security are political problems. Not all political conflicts are security issues. In other words, policy acquires a dual aspect - of dispute and security issues- when you lost lives or materials damages or have become a possibility, in the point of view of one or more involved actors.